Statistical Equations to Estimate the In-situ Concrete Compressive Strength from Non-destructive Tests (Journal of Engineering, 2018)
The aim of this study is to propose reliable equations to estimate the in-situ concrete compressive strength from the non-destructive test. Three equations were proposed: the first equation considers the number of rebound hummer only, the second equation consider the ultrasonic pulse velocity only, and the third equation combines the number of rebound hummer and the ultrasonic pulse velocity. The proposed equations were derived from non-linear regression analysis and they were calibrated with the test results of 372 concrete specimens compiled from the literature. The performance of the proposed equations was tested by comparing their strength estimations with those of related existing equations from literature. Comparisons revealed that the proposed ultrasonic pulse velocity and combined equations achieved better agreements with the test results than the related existing equations, whereas the proposed and the existing rebound hummer equations were inconsistent.